Al-Qur’an Based Education in Integrated Islamic Elementary School - Hasan Basri (IAIN Batusangkar, 2026)
This study aims to describe the curriculum and learning format based on the al-Qur'an in schools at SDT al-Wahdah Kendari. Data collection in this case study uses document studies, interviews, and observations. Data analysis is carried out using curriculum integration theory and learning process theory. The results of the study indicate that al-Qur'an-based learning is carried out by incorporating memorization learning of the al-Qur'an into the construction of the school curriculum with a larger time allocation, reaching 55.45% of the total 50.5 hours of lessons in a week. Al-Qur’an learning consists of reading lessons using the Iqro' method in tahsin and memorizing with a target of 3 juz which is gradual each semester, as well as the integration of the contents of the al-Qur'an in learning carried out by teachers by connecting it with science to strengthen students' faith and obedience, in implementing religious teaching and controlling its practice through a refraction approach, examples, stories, and advice. Keywords: Al-Qur'an based education, curriculum integration, Integrated Islamic Elementary School